Effects of Halo Spin on the Formation and Evolution of Bars in Disk Galaxies - Jang, Dajeong; Kim, Woong-Tae (The Astrophysical journal, 2024)
The spin of dark halos has been shown to significantly affect bar formation and evolution in disk galaxies. To understand the physical role of halo spin in bar formation, we run N -body simulations of isolated, Milky Way–sized galaxies by varying the halo spin parameter in the range −0.16 ≤ λ ≤ 0.16 and the bulge mass. We find that our adopted halo alone is subject to swing amplification of an m = 2 nonaxisymmetric mode rotating in the same sense as the halo, which assists or inhibits the bar formation in a disk depending on its sense of rotation. The m = 2 mode in the disk, growing via swing amplification, interacts constructively (destructively) with the m = 2 mode in the prograde (retrograde) halo, promoting (delaying) bar formation. A bar grows by losing its angular momentum primarily to a halo. Since the halo particles inside (outside) the corotation resonance with the bar can emit (absorb) angular momentum to (from) the bar, the bar pattern speed decays more slowly for larger λ > 0, while it decreases relatively fast almost independent of λ ≤ 0. Models with a strong bar develop a boxy peanut-shaped bulge. In models without a bulge, this occurs rapidly via buckling instability, while bars with a bulge thicken gradually without undergoing buckling instability. Among the models considered in the present work, the bar in the λ = 0.06 model with a bulge of 10% of the disk mass best describes the Milky Way in terms of its length and pattern speed.